Strong convergence of a modified extragradient algorithm to solve pseudomonotone equilibrium and application to classification of diabetes mellitus - Cholamjiak, Watcharaporn; Suparatulatorn, Raweerote (Chaos, solitons and fractals, 2023)
This work studies pseudomonotone equilibrium problems. The modified inertial viscosity subgradient extragradient is proposed for obtaining strong convergence, and it is proved under the assumption that the bifunction satisfies the Lipchitz-type condition. Flexible use of different stepsize parameters is offered. Moreover, the proposed algorithm is applied to solve diabetes mellitus classification problems. The algorithm’s efficiency is shown by comparing with many existing methods with 80.3% high accuracy. The training-validation loss and accuracy plots are presented to consider our good model fitting. •The paper proposed an algorithm for solving pseudomonotone equilibrium problems.•The strong convergence result has been established subject to certain conditions.•Predict diabetes mellitus through the proposed algorithm by ELM.•The algorithm’s effectiveness is up to 80.3% accuracy.